2020
DOI: 10.15537/smj.2020.3.24916
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge, attitudes and practices of Saudi adults about calorie labeling in central Saudi Arabia

Abstract: To assess the knowledge, attitudes, and practices of adults regarding the implementation of calorie labeling in restaurants in Riyadh, Saudi Arabia. Methods: This was a cross-sectional study of 1443 adults invited to complete a self-administered questionnaire consisting of 4 parts that assess demographics, knowledge, attitudes, and practices of mandatory menu labeling. The survey was conducted in all 5 regions of Riyadh. Results: We entered 1265 surveys into final data analysis with a response rate of 88%. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 21 publications
2
15
2
Order By: Relevance
“…14 Moreover, a study conducted by Alassaf et al in Saudi Arabia showed similar results to our study, where half of the participants changed their order according to the CCD. 10 However, the increase in the percentage of the Dumanovsky et al's study after the enforcement is almost double the percentage in the present study. There are two probable causes for this difference, the first being the fact that the customers there were already using the CCD and were familiar with the concept of CCD in menus before the enforcement, unlike the customers in our study, where they were not familiar with the concept of CCD in restaurants before the implementation in January 2019.…”
contrasting
confidence: 65%
See 3 more Smart Citations
“…14 Moreover, a study conducted by Alassaf et al in Saudi Arabia showed similar results to our study, where half of the participants changed their order according to the CCD. 10 However, the increase in the percentage of the Dumanovsky et al's study after the enforcement is almost double the percentage in the present study. There are two probable causes for this difference, the first being the fact that the customers there were already using the CCD and were familiar with the concept of CCD in menus before the enforcement, unlike the customers in our study, where they were not familiar with the concept of CCD in restaurants before the implementation in January 2019.…”
contrasting
confidence: 65%
“…To our knowledge, this study is the first to address the topic of CCD in the Middle East using a mixed method approach, aiming to know its effect on customers eating behaviors, and the effect of customers sociodemographics, health status, knowledge, and health habits on checking the CCD. Although the topic has been explored very briefly, 8,10 we have uniquely explored the calories ordered by each customer using the customers' receipts. Thus, ensuring the accuracy of comparisons made in this study.…”
Section: Strengths Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Exposure to calorie information over time through restaurant menus might increase consumer awareness of calories, encourage healthy food choices, help to reduce calorie consumption, change people's attitudes, and make them pay more attention when ordering food from restaurants [8,9]. Recent studies in the Saudi population have assessed the knowledge, attitudes, and practice of utilizing caloric information in restaurant menus and found that 24-50% utilized the caloric information on menus when purchasing meals from restaurants [10][11][12].…”
Section: Introductionmentioning
confidence: 99%